Respiratory follow-up pre- and post-engineering controls or cessation of added diacetyl at four microwave popcorn facilities. Issue 3 (12th August 2019) - Lockey, James E.; Hilbert, Timothy J.; LeMasters, Grace; Dunning, Kari K.; McKay, Roy T.; Levin, Linda S.; Rice, Carol H.
We previously reported significant cross-sectional decrements in forced expiratory volume in 1 s (FEV1 ) from 2005 to 2006 among mixing room employees (mixers) with exposure to the butter flavouring diacetyl at four US microwave popcorn facilities [1]. Other studies with similar findings have been summarised by the US National Institute for Occupational Health and Safety (NIOSH) [2]. Diacetyl (2, 3-butanedione) is a soluble diketone that vaporises when heated. Though use in the popcorn industry has declined, diacetyl has been documented in cigarette smoke, electronic cigarettes and coffee [2]. The aim of this follow-up study was to examine lung function in three cohorts. Cohort 1 began their employment before 2003, and aimed to identify any significant longitudinal decline among those with higher exposures and less extensive exposure controls. Cohort 2 began their employment between 2003 and 2007, and examined the impact of changes after implementation of additional exposure controls. Cohort 3 began their employment during or after 2008, when added diacetyl use was discontinued. These cohorts included all current full-time employees at the four facilities tested previously. Informed consent, and pulmonary and work histories were collected. In a 7-year study at 4 microwave popcorn facilities, mixing room employees exposed to diacetyl prior to the introduction of respirators showed significant loss of lung function but did not continue to decline longitudinally faster than other job categories http://bit.ly/2xwWRiw